Florida State Symbols - Martin B. Main; Ginger M. Allen (EDIS, 2005)
Florida has a diversity of habitats that support a rich flora and fauna. Ponce DeLeon, who explored Florida in 1513 in search of the mythical “Fountain of Youth,” recognized Florida for its beauty. DeLeon claimed Florida for Spain and named this new land “Pascua de Florida,” which translates as “feast of flowers.” Florida was sold to the United States in 1819 and became the 27th state of the United States on March 3, 1845. Today, Florida is known as the Sunshine State. The state capitol resides in Tallahassee. In honor of Florida's natural resources, state legislators have identified several state symbols. This document is Circular 1467, one of a series of the Department of Wildlife Ecology & Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication Date: May 2005.